1971
DOI: 10.1111/j.1399-0039.1971.tb00089.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic HL‐A Antibodies: Immunoglobulin Classification

Abstract: Leukocyte antibodies were fractionated by sucrose gradient ultracentrifugation, and it was found that antibodies are present in the IgG immunoglobulins in the majority of the cases. However, it was possible to demonstrate antibody activity in the IgM as well as the IgG fraction of sera originating from immunized volunteers, pregnant women, and patients with transfusion reactions caused by leukocyte antibodies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1976
1976
2013
2013

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…It can be seen that in only one case is there evidence of inhibition by a 'supernatant' fraction and this is very slight. All the serum 'supernatant' fractions tested in these experiments were also tested in a cytotoxic assay and were shown to have retained specific cytotoxic antibody, presumably 7 s. Most specific antibodies in multiparous sera have been found to be 7 s (Ahrons & Glavind-Kristensen 1971). In some experiments complement was added to cells which had been preincubated with serum 'supernatants' and washed ready for rosette formation, t o test for bound cytotoxic antibody.…”
Section: Icesultsmentioning
confidence: 99%
“…It can be seen that in only one case is there evidence of inhibition by a 'supernatant' fraction and this is very slight. All the serum 'supernatant' fractions tested in these experiments were also tested in a cytotoxic assay and were shown to have retained specific cytotoxic antibody, presumably 7 s. Most specific antibodies in multiparous sera have been found to be 7 s (Ahrons & Glavind-Kristensen 1971). In some experiments complement was added to cells which had been preincubated with serum 'supernatants' and washed ready for rosette formation, t o test for bound cytotoxic antibody.…”
Section: Icesultsmentioning
confidence: 99%
“…Since in preliminary experiments IgC prepared by ion exchange chromatography of serum CMD shows only peak A of cytotoxic activity after IEF, it is tempting to speculate that IgM and/or highly charged IgG molecules (known to be relatively depleted by ion exchange chromatography) are important in the crossreactive activity observed in CMD and perhaps important in cross-reactivity in other anti-HL-A sera. IgM anti-HL-A antibodies have been reported (Stocker et al 1969, Ahrons & Glavind-Kristensen 1971, Colombani et al 1973) although most reports emphasize that the activity is predominantly IgG (Metzgar & Seigler 1967, Williams et al 1971 Glavind-Kristensen 197 1). However, in previously reported work ) on focused fractions of BC p-B, peak C, not peak A, was depleted in cross-reactivity suggesting that more than one mechanism may be involved.…”
Section: Disc Us F I Onmentioning
confidence: 99%
“…[20][21][22][23] Patients with primary RM have a prevalence of HLA antibodies of maximum 10%; 24,25 patients with secondary RM on the other hand may have a high prevalence of HLA antibodies. 26 Steinborn et al 27 found an association between an increased prevalence of HLA antibodies and placental abruption.…”
Section: Hla Antibodiesmentioning
confidence: 99%